EFFECTS OF ENVIRONMENTAL FACTORS ON REPRODUCTIVE HEALTH - Palvonova Raykhon Umidulla qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Reproductive fitness refers to physical, emotional, social and well-being disorders associated with the reproductive system. Genetics and organic elements have a significant impact on reproduction outcomes, but environmental factors have grown to become increasingly important determinants of reproductive fitness. Over the past decades, environmental awareness of contamination, chemicals and toxins has been linked to many adverse effects on reproductive fitness, including infertility, miscarriage, premature babies, and developmental disorders. These environmental pollution affect all male and reproductive systems for the effects of men and loud voice, and in some cases can have cross-generational consequences.